Maximal commutators and commutators of potential operators in new vanishing Morrey spaces. (March 2020) - Almeida, Alexandre
Abstract: We study mapping properties of commutators in certain vanishing subspaces of Morrey spaces, which were recently used to solve the delicate problem of describing the closure of nice functions in Morrey norm. We show that the vanishing properties defining those subspaces are preserved under the action of maximal commutators and commutators of fractional integral operators.